2022
DOI: 10.1093/infdis/jiac301
|View full text |Cite
|
Sign up to set email alerts
|

Increased Macrophage-Specific Arterial Infiltration Relates to Noncalcified Plaque and Systemic Immune Activation in People With Human Immunodeficiency Virus

Abstract: Background Persistent immune activation is thought to contribute to heightened atherosclerotic cardiovascular disease (ASCVD) risk among people with HIV (PWH). Methods Participants (≥18 years) with versus without HIV and without history of clinical ASCVD were enrolled. We hypothesized that increased macrophage-specific arterial infiltration would relate to plaque composition and systemic immune activation among PWH. We applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
5
1
Order By: Relevance
“…Further, select immune parameters associated significantly with CVD risk surrogates among WWH but not among men with HIV [25]. Conversely, in our current study, we did not find higher levels of inflammatory monocytes among WWH on ART compared to women without HIV, while among predominately male cohort of PWH on ART in separate study recruited from the same geographic region and similar entry criteria, we did find higher levels of inflammatory monocytes among PWH on ART [26]. To elucidate immune mechanisms contributing to heightened CVD risk specifically among WWH, we need more studies which either focus exclusively on WWH or which robustly enroll WWH, thereby enabling the performance of appropriately powered sex-stratified analyses.…”
Section: Plos Onecontrasting
confidence: 82%
“…Further, select immune parameters associated significantly with CVD risk surrogates among WWH but not among men with HIV [25]. Conversely, in our current study, we did not find higher levels of inflammatory monocytes among WWH on ART compared to women without HIV, while among predominately male cohort of PWH on ART in separate study recruited from the same geographic region and similar entry criteria, we did find higher levels of inflammatory monocytes among PWH on ART [26]. To elucidate immune mechanisms contributing to heightened CVD risk specifically among WWH, we need more studies which either focus exclusively on WWH or which robustly enroll WWH, thereby enabling the performance of appropriately powered sex-stratified analyses.…”
Section: Plos Onecontrasting
confidence: 82%
“…These changes are notable, as specific inflammatory pathways have been hypothesized to increase the risk of CVD in PWH . Prior studies have shown increased arterial inflammation using fludeoxyglucose-18 positron emission tomography in PWH compared with controls without HIV in the general population, linking arterial inflammation to noncalcified plaque among PWH . In this regard, LpPLA2 is a platelet-activating factor that hydrolyzes oxidized lipids, thought to play a proinflammatory role in atherogenesis and is a marker of arterial inflammation in PWH .…”
Section: Discussionmentioning
confidence: 99%
“… 4 Prior studies have shown increased arterial inflammation using fludeoxyglucose-18 positron emission tomography in PWH compared with controls without HIV in the general population, 37 linking arterial inflammation to noncalcified plaque among PWH. 38 In this regard, LpPLA2 is a platelet-activating factor that hydrolyzes oxidized lipids, thought to play a proinflammatory role in atherogenesis and is a marker of arterial inflammation in PWH. 39 , 40 In contrast, markers of generalized inflammation, such as CRP, may not be increased in well-treated PWH taking antiretroviral therapy, potentially explaining the more modest changes in CRP observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because caspase-1 is more proximally involved in the inflammasome pathway, subtle transcriptional or translational changes that are difficult to detect may lead to larger, more apparent changes in downstream mediators such as IL-18 or IL-1β. We previously observed an effect of caspase-1 in the relationship of macrophage-specific arterial inflammation in PWH, but in this study we assessed coronary plaque, which may have a differential relationship to more downstream components of the inflammasome [ 12 ]. Moreover, despite IL-18 and IL-1β being byproducts of inflammasome activation, IL-18 had a relatively larger association with Leaman score than IL-1β (although with overlapping confidence intervals).…”
Section: Discussionmentioning
confidence: 99%